2017
DOI: 10.3386/w24117
|View full text |Cite
|
Sign up to set email alerts
|

On the Estimation of Treatment Effects with Endogenous Misreporting

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 3 publications
(3 reference statements)
0
38
0
Order By: Relevance
“…If self-reported measures must be used, it would be well-advised to address potential endogeneity arising from selective misreporting. To this effect, researchers can even explicitly model misreporting following the novel approaches of Almada et al (forthcoming) and Nguimkeuy et al (2016). We expect this area of research to grow as awareness spreads regarding the severity of this important yet oft-overlooked source of endogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…If self-reported measures must be used, it would be well-advised to address potential endogeneity arising from selective misreporting. To this effect, researchers can even explicitly model misreporting following the novel approaches of Almada et al (forthcoming) and Nguimkeuy et al (2016). We expect this area of research to grow as awareness spreads regarding the severity of this important yet oft-overlooked source of endogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of articles analyzing the impact of measurement error in a binary independent variable on estimated regression coefficients (Aigner ; Bollinger ; Hausman et al ; Lewbel ; Hu ; DiTraglia and Garcia‐Jimeno ; Hu et al ; Nguimkeu et al ). Here, we derive the bias in OLS and IV both for the case where the measurement error is exogenous and where it is endogenous, for a simple model with no additional covariates other than the binary variable (for a derivation of bias with an additional covariate vector, see Nguimkeu et al ).…”
Section: A Brief Theoretical Analysis Of Bias From Measurement Error mentioning
confidence: 99%
“…A growing literature documents the problems with relying on survey measures of program participation, which suffer from significant reporting error, when conducting impact evaluations (Meyer, Mok, and Sullivan, 2015;Mittag, 2016;Nguimkeu et al, 2017). Administrative data are ordinarily assumed to be the "gold standard" to overcoming these econometric challenges, but relatively little evidence exists on the potential problems with administrative records or econometric strategies to address them.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the expected negative relationship between SNAP and food insecurity (Van Hook & Ballistreri, 2006;Nord & Prell, 2011;Schmidt et al, 2016), but others have found statistically insignificant or even positive associations (Gundersen & Oliveira, 2001;Hofferth, 2004;Huffman & Jensen, 2003;Wilde et al, 2005;Hoynes & Schanzenbach, 2015). SNAP is also often found to be positively correlated with obesity, but some studies find insignificant or negative effects (Meyerhoefer and Pylypchuk, 2008;Gundersen, 2015;Nguimkeu et al, 2017;Denteh, 2017).…”
Section: Introductionmentioning
confidence: 99%